Sustainable Supply Chains- A Study of Company Practices Through Analysis of Corporate Reporting Trends within Listed Retail and Consumer Goods Companies in the EU and US - Nanayakkara, Udaya / U.A. (2011)
This report addresses the supply chains of companies through the lens of sustainability and related corporate reporting. The project was conceived as part of the requirement of a client organisation to select ‘leaders’ and poorer performing companies on an investment portfolio for shareholder engagement. Existing company reporting within the listed retail and consumer goods companies in the UK, US and Rest of EU was scored and analysed using a developed evaluation framework to unearth trends. While overall scores in sections of the evaluation provided for an overview of practices across-the-board, in examining data for unearthing the trends in corporate reporting and sustainability practices on supply chains, analysis was conducted across evaluation categories, regions and industry sectors. While identifying leaders and poor performing companies, a number of characteristics identified in literature in the area such as prevalence of policy, sectorial and regional variations were confirmed. New trends related to governance, risk and sustainability performance management emerged, bringing to the surface related questions for further investigation. The study concludes three main recommendations on how companies could evolve its current supply chain practice on sustainability; that companies need to be induced towards integrative practices via a business case, that there should be transparency from all stakeholders involved in performance rating, and the case for an alternative model to rating historical performance for evaluation.